2010
DOI: 10.1186/1471-2105-11-s1-s21
|View full text |Cite
|
Sign up to set email alerts
|

Learning to predict expression efficacy of vectors in recombinant protein production

Abstract: BackgroundRecombinant protein production is a useful biotechnology to produce a large quantity of highly soluble proteins. Currently, the most widely used production system is to fuse a target protein into different vectors in Escherichia coli (E. coli). However, the production efficacy of different vectors varies for different target proteins. Trial-and-error is still the common practice to find out the efficacy of a vector for a given target protein. Previous studies are limited in that they assumed that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Then they applied bioinformatics analysis on the data to determine the key factors for a gene to yield a soluble expression product. According to Chan et al [3], most previous works only investigated protein solubility related factors, and considered together the genes that formed inclusion fraction, and the genes did not express, as the negative samples. But in this study, they built a model to predict whether a vector-protein pair will be expressed in E. coli.…”
Section: Recombinant Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Then they applied bioinformatics analysis on the data to determine the key factors for a gene to yield a soluble expression product. According to Chan et al [3], most previous works only investigated protein solubility related factors, and considered together the genes that formed inclusion fraction, and the genes did not express, as the negative samples. But in this study, they built a model to predict whether a vector-protein pair will be expressed in E. coli.…”
Section: Recombinant Prmentioning
confidence: 99%
“…Based on our literature review, the proposed features in [3] and [16] studies were chosen to generate sequence features. The selection criteria were relevance and the achieved performance.…”
Section: Feature Generationmentioning
confidence: 99%
“…Interestingly, bioinformatics studies have already shown that primary sequence characteristics have great impact on protein overexpression in E. coli [28]. To explore this relationship further, some useful bioinformatics prediction tools have been established, such as the Wilkinson-Harrison prediction model [29], multiple linear regression fit model [30], solubility index-based model [13], support vector machine (SVM)based model [31,32], PROSO model [12], SOLpro model [33] and PROSO II [14]. One recent review critically summarized the strengths and limitations of seven proposed protein solubility prediction tools in terms of prediction accuracy, Matthews correlation coefficient and data size of studies [22].…”
Section: Challenges In Process Development For Soluble Protein Expresmentioning
confidence: 99%
“…Several prediction models have been established (6,9), such as the Harrison prediction model (10), multiple linear regression (MLR) model (11), solubility index-based model (12), support vector machine-based model (13,14), PROSO model (15), SOLpro model (16), cc SOL model (17) and PROSO II model (18). These bioinformatics models can significantly reduce trial and error procedures involved in optimization of expression systems to increase the soluble expression level of heterologous proteins.…”
Section: Introductionmentioning
confidence: 99%